Levels of Mathematical Modeling in Medicine and Medical Diagnostics - Bozorov Erkin Hodjievich; Kubaev Asaliddin Esirgapovich; Hodjieva Mokhlaroim Erkin qizi (Scholars Digest Publishing, 2023)
This article provides a scientific analysis of the features, goals and the simplest ways to implement the interactive educational method "Brainstorming" used in teaching the subject "Mathematical Modeling in Medicine and Medical Diagnostics", and the positive results obtained ensure the free participation of students in the educational (discussion)) process.
Keywords: Mathematical modeling, medical diagnosis, model analysis, terminology, artificial intelligence, algorithm, functional connection, initial velocity, coordinate.